Strategi Pemasaran Keripik Singkong Cap Kelinci Industri Rumah Tangga di Tanjung Morawa Kabupaten Deli Serdang - Supriadi Harahap; Khairul Saleh; Gustami Harahap (Universitas Medan Area, 2021)
This study aims to the strengths, weaknesses, opportunities and threats to the marketing of cassava chip home industry and to determine the marketing strategy of cassava chip home industry stamp rabbit chips in Tanjung Morawa District, Deli Serdang Regency. The research method used was Snowball Sampling. Research samples were 33 samples. Based on the research, one producer was found, then two traders from the producer, then five retailers took from the collecting trader, and twenty- five consumers who bought from the retailer of cassava stamp rabbit chips. Data collection methods use primary and secondary data. Data analysis method used is descriptive analysis with the SWOT analysis method by identifying internal. Avoid referrals and unusual evaluation (IFE) and identifying external factor evaluation (EFE), followed by searching for the right strategy through the IE matrix and the SWOT matrix. The results of this study indicate that rabbit stamp cassava chips in Tanjung Morawa Subdistrict Deli Serdang Regency which is running a progressive strategy signifies a strong effort and opportunity to be developed. By taking an SO strategy from the results of the questionnaire, it can be obtained by maintaining and maintaining the superiority of the product can increase the demand for cassava chips rabbit stamp is getting higher, and utilizing a strategic location and the possibility of increasing collection traders, making it easier for the process to market the product to retailers abbreviations. Cambria 10, with one line spacing (1) spacing. In Indonesian.